Chemistry and biological activities of Ailanthus altissima Swingle: A review - Martino, Laura De; Feo, Vincenzo De (Pharmacognosy Reviews)
Ailanthus altissima (Mill.) Swingle, [syn. = A. glandulosa Desf.] (Simaroubaceae), is a large tree indigenous to China. It is known as the “Tree of Heaven” and has been the subject of several chemical and biological studies. It is used in traditional medicine in many parts of Asia, including China, to treat cold and gastric diseases as diarrhea, dysentery, and endoparasites. It is also used as a bitter-aromatic drug and as an antitumoral. The chemical studies have underlined the presence of various classes of compounds, the main being quassinoids and alkaloids. The extracts of this plant, as well as pure isolated compounds, showed multiple pharmacological activities such as antitumor, antiviral, insecticidal, herbicide and others. In particular, 1- methoxycanthin-6-one has been proposed as an anticancer chemotherapeutic agent. In this review, we have explored chemistry and biological activities of A. altissima, in order to comprehend and synthesize its potential image of multipurpose medicinal agent. The plant is widely cultivated to large regions of the world and its importance, as a medicinal plant, is growing up substantially with increasing and stronger reports in support of its multifarious therapeutic uses.
Keywords: Ailanthus altissima; Simaroubaceae; Quassinoids; Alkaloids; Chemical constituents; Biological activities